The δ18O signatures of HCl‐extractable soil phosphates: methodological challenges and evidence of the cycling of biological P in arable soil. (17th August 2015) - Amelung, W.; Antar, P.; Kleeberg, I.; Oelmann, Y.; Lücke, A.; Alt, F.; Lewandowski, H.; Pätzold, S.; Barej, J. A. M.
Summary: Soil phosphates exchange oxygen atoms rapidly with soil water once recycled by intracellular enzymes, thereby approaching an equilibrium δ 18 OP signature that depends on ambient temperature and the δ 18 OW signature of soil water. We hypothesized that in the topsoil, phosphates reach this equilibrium δ 18 OP signature even if amended by different fertilizers. In the subsoil, however, there might be phosphates with a smaller δ 18 OP value than that represented by the isotopic equilibrium value, a condition that could exist in the case of limited biological P cycling only. We tested these hypotheses for the HCl‐extractable P pool of the Hedley fractionation scheme of arable soil in Germany, which integrates over extended time‐scales of the soil P cycle. We sampled several types of fertilizer, the surface soil that received these fertilizer types and composites from a Haplic Luvisol depth profile under long‐term agricultural practice. Organic fertilizers had significantly smaller δ 18 OP values than mineral fertilizers. Intriguingly, the fields fertilized organically also tended to have smaller δ 18 OP signatures than other types of surface soil, which calls into question full isotopic equilibrium at all sites. At depths below 50 cm, the soil δ 18 OP values were even depleted relative to the values calculated for isotopic equilibrium. This implies that HCl‐extractable phosphates in different soil horizons are of different origins. In addition, it supports the assumption that biological cycling of P by intracellular microbial enzymes might have been relatively inefficient in the deeper subsoil. At depths of 50–80 cm, there was a transition zone of declining δ 18 OP values, which might be regarded as the first evidence that the degree of biological P cycling changed at this depth interval.